Rancang Bangun Aplikasi Tracer Study Berbasis Website pada SMAN 20 Surabaya - Pratama, Denny Putra Yudha; Setyawan, Henry Bambang; Ningsih, Norma (Jurnal Sistem Informasi Universitas Dinamika, 2022)
SMAN 20 Surabaya is a school with an average number of graduates per year as many as 300 graduates. SMAN 20 Surabaya conducts a tracer study once a year which is important in order to obtain information that can support improvement or determine academic policies to improve the quality of education and is an important part of accreditation assessment. There are problems that arise in the implementation of the tracer study at this time, namely SMAN 20 Surabaya does not have a clear reference or implementation guide, there is no tracer study implementation for graduate users, there is the possibility of redundancy or duplication of data, making questionnaires is often delegated causing the need to request access to control tracer study process, there is no feedback from alumni related to the learning process, there is no focus on the graduation year of the alumni who are the target respondents, and the report on the results of the tracer study is only a table listing responses from alumni. Therefore, it is necessary to have a tracer study application that is able to overcome these problems. The tracer study method is used as a reference for a series of tracing processes in the application. The process starts from making a questionnaire, then the process of collecting data / filling out the questionnaire, and finally the process of analyzing the data that will be poured into the report. The results of the research are that this application is able to provide questionnaires for alumni and graduate users, can record filling out questionnaires from respondents, has user access rights sharing, generates feedback for schools to improve education quality, can recommend alumni as questionnaire targets, and presents a summary dashboard that contains information that can support the improvement of the quality of school education.